2016
DOI: 10.1371/journal.pone.0162089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anthocyanin on Serum Lipids in Dyslipidemia Patients: A Systematic Review and Meta-Analysis

Abstract: BackgroundDyslipidemia was present in most of the patients with coronary heart disease. Epidemiological evidence suggests that anthocyanin has some effects on the serum lipid. However, these results are controversial. This study aimed at collecting current clinical evidence and evaluating the effects of anthocyanin supplementation on total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C) in dialysis patients.MethodsThe search inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 21 publications
4
50
1
1
Order By: Relevance
“…In addition, platelet chemokines are produced following stimulation of TNF-α and IL-1β [68], which result in recruitment of leukocytes to the site of vascular injury and enhancement of inflammatory processes. Recently, some studies have revealed that anthocyanin supplementation significantly reduces the serum lipid [69] and pro-inflammatory cytokine levels [7072], consistent with the effects of anthocyanins observed in our previous studies [32, 35]. In the present study, we first revealed that the reductions in the platelet chemokine levels caused by anthocyanins were positively correlated with the changes in the inflammatory marker and blood lipid levels.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, platelet chemokines are produced following stimulation of TNF-α and IL-1β [68], which result in recruitment of leukocytes to the site of vascular injury and enhancement of inflammatory processes. Recently, some studies have revealed that anthocyanin supplementation significantly reduces the serum lipid [69] and pro-inflammatory cytokine levels [7072], consistent with the effects of anthocyanins observed in our previous studies [32, 35]. In the present study, we first revealed that the reductions in the platelet chemokine levels caused by anthocyanins were positively correlated with the changes in the inflammatory marker and blood lipid levels.…”
Section: Discussionsupporting
confidence: 91%
“…For example, systematic reviews of the effects of interventions with ANCs on lipid biomarkers have reported that only ANCs cause significant reductions in LDL-C in participants with hypercholesterolemia (4 out of 4 studies), but not in participants who had normal cholesterol (zero out of 8 studies) [172]. It was also reported that ANCs supplementation significantly decreased T-C, TAGs, LDL-C and increased HDL-C in dyslipidemic patients (6 studies including 586 subjects [173]. Similarly, it has been reported that high-dose quercetin supplementation caused a significant reduction in blood pressure in stage 1 hypertensive participants but was not affected in pre-hypertensive participants [174].…”
Section: Discussionmentioning
confidence: 99%
“…Though having similarities in terms of TC and LDL level we have also assessed effect of anthocyanins on HDL, TG, apolipoprotein A-1 and B, and inflammatory markers. Similarly, even Liu et al [9] have published the effect of anthocyanins on serum lipid levels in exclusive dyslipidemic patients; in contrast to them we have included all the population including healthy adults and assessed impact of purified or dietary supplementations on lipid levels. We found that results of our meta-analysis are far more reliable as Egger's regression and Begg and Mazumdar rank correlation test showed no publication bias for all the parameters.…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficacy studies of natural phenolic compounds are often subjected to criticism regarding dosage standardization and reproducibility of their effects in various health conditions. Similarly in general, all studies favour the supplementation of anthocyanin for improvement of lipid profile in healthy, diabetic, and populations at risk of CVD, although some studies have failed to report any significant improvement or reported varying degrees of improvement in various dyslipidemias and inflammatory markers with therapeutic intervention of anthocyanins [9]. We herewith investigated the cumulative evidence from 17 randomized controlled trials (RCT) [1027] for the association of anthocyanin consumption (either dietary sources or supplements) with levels of various lipid and inflammatory markers.…”
Section: Introductionmentioning
confidence: 99%